Concept development of family farms in Ukraine, from the experience of foreign countries - Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2017)
It studies the preconditions of creation, functioning of farms in Ukraine and foreign countries. In the course of the study revealed that over the years 1990-2015, the number of farms increased from 332 to 54 302 is 915, 40 thousand hectares of land. For a specified period on one farm had between 12.0 to 78.8 ha of agricultural land (the most notable growth occurred in the period from 1990-1995, he was almost 100 times). Despite this, farming did not become efficient producers of agricultural products. In contrast, in the world more than 500 million farms (87,7%) of the total number belong to families that produce 56% of such production. In the US, family farms handle 78% of the agricultural land of the country, producing 84% of all agricultural products worth 230 billion dollars. In foreign countries is significantly different size of farms. In North America for a farmer falls from 190,0 to 600,0 ha, in most of the countries of Asia and Africa – 2,0 - 100,0 ha of land in Australia and New Zealand from 2 to 20 thousand hectares, and the like. In the EU land farms range from 2,0 – 500,0 ha. These countries are moving towards support of small, home gardens and farms. The results of the research showed that farmers that are the main producers of agricultural products in the developed world are high-performance enterprises despite the size of the economy, because in these countries there is a deliberate policy to support agricultural producers to improve production efficiency, ensuring sustainable land management. The competitiveness of these farms is justified by the presence of the developed forecasting and planning their development strategies. Besides, in world practice there are three main types of enterprise development strategies, each of which is fully justified by the specificity of production: growth strategy (development), a strategy of constancy and survival strategy.From the experience of foreign countries, to achieve efficient, ecological and safe agricultural land use in the article the concept of development of family farming, key aspects of which are: 1) rehabilitation Institute of farming; 2) to regulate the size of the land to create farms from 2.0 500.0 ha, taking into account prospects of development of these farms and their specialization; 3) development of land management projects concerning ecological-economic substantiation of crop rotation and streamline land – the basis of compliance with environmentally sound land management; 4) creation of an agrarian Bank, the special purpose of which would be the service of production and not the circulation of land sub-divisions at the regional level with the aim of establishing cooperation with producers of agricultural products; 5) extension of long-term loans commodity, interest rate subsidies, to establish tax incentives which would foster the development of farms and agricultural businesses in General; 6) development of consumer cooperation, which is an efficient mechanism of delivering products to consumers; 7) ensuring the stability of the purchase prices for agricultural products; 8) improving the mechanism of state regulation of agricultural imports in favor of domestic producers; 9) the implementation of farms of family type with a clear definition of its participants and addressing the possibility of involvement of hired labor for these farms; 10) the organization of training of farmers in the developed world, with the aim of acquiring skills in management and economic activities. Keywords: farm, family farm, college, concept development, foreign experience.